1992
DOI: 10.1029/92jd01812
|View full text |Cite
|
Sign up to set email alerts
|

Airborne flux measurements of trace species in an Arctic boundary layer

Abstract: In situ airborne measurements of the turbulent flux and mean values for O3, CO, and CH4 were obtained in the boundary layer over selected wetland systems in Alaska. These measurements were obtained in July–August 1988 as part of the NASA Global Tropospheric Experiment Program's Arctic Boundary Layer Expedition (ABLE 3A). The flux measurements obtained from this study provide information on the source/sink distribution of O3 and CH4 over the Yukon‐Kuskokwim Delta (YKD) and Alaskan North Slope (ANS) regions of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 57 publications
(30 reference statements)
0
21
0
3
Order By: Relevance
“…It showed the kind of spatial flux variations that can be obtained at the regional scale. A comparison with chamber methane fluxes scaled-up using satellite imagery (Bartlett and Harriss 1993) gave a similar spatial integrated value for the summertime period to the one found by Ritter et al (1992) on 9 August 1988. Crill (1991) measured the seasonal pattern of methane consumption of a temperate woodland soil, using closed chambers at the same location.…”
Section: Spatial and Temporal Variability Of Methane Fluxesmentioning
confidence: 60%
See 2 more Smart Citations
“…It showed the kind of spatial flux variations that can be obtained at the regional scale. A comparison with chamber methane fluxes scaled-up using satellite imagery (Bartlett and Harriss 1993) gave a similar spatial integrated value for the summertime period to the one found by Ritter et al (1992) on 9 August 1988. Crill (1991) measured the seasonal pattern of methane consumption of a temperate woodland soil, using closed chambers at the same location.…”
Section: Spatial and Temporal Variability Of Methane Fluxesmentioning
confidence: 60%
“…1995, personal communication). Ritter et al (1992) did a survey flight over Alaska's Yukon-Kuskokwim Delta, from which they were able to extrapolate a contour-plot of methane flux superimposed to the land cover types. It showed the kind of spatial flux variations that can be obtained at the regional scale.…”
Section: Spatial and Temporal Variability Of Methane Fluxesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the high variation between CO uptake and emission rates does not yet allow us to classify the ecosystem types or climatic regions. Tall tower (Andreae et al, 2015) and airborne measurements have indicated source areas of CO both in the Amazon basin (Harriss et al, 1990) and in the North American tundra (Ritter et al, 1992(Ritter et al, , 1994 suggesting a connection between high plant biomass and biological CO forming processes.…”
Section: Introductionmentioning
confidence: 99%
“…Airborne EC has elucidated surface-atmosphere exchange processes for more than 3 decades (Dabberdt et al, 1993;Desjardins et al, 1982;Lenschow et al, 1981;Ritter et al, 1992Ritter et al, , 1994Ritter et al, , 1990Sellers et al, 1997). Recent GHG applications include evaluations of net ecosystem exchange (NEE) over complex ecosystems (Miglietta et al, 2007;Zulueta et al, 2013) and quantification of CH 4 emissions from shale gas production regions , agricultural areas (Desjardins et al, 2018;Hiller et al, 2014), and Arctic biomes (Sayres et al, 2017).…”
Section: Introductionmentioning
confidence: 99%